Enhancement of human lymphocyte proliferative response to purified protein derivative by an anti-interleukin-2 receptor alpha chain antibody (CD25) - Kasinrerk W. (2014)
While it is clear that the beta subunit of interleukin-2 receptor (IL-2R) plays a pivotal role in IL-2-induced signal transduction, the function of the alpha subunit, other than modulating the association rate of IL-2, is still unknown. It has been reported that the interaction between IL-2 and the IL-2R alpha subunit of several IL-2-dependent murine T-cell lines may result in a negative regulatory signal. To confirm this finding, we investigated the effect of an anti-IL-2R alpha antibody, CD25-8D8, on the proliferative response of human peripheral blood lymphocytes. Lymphocytes from purified protein derivative (PPD)-positive donors were cultured with PPD and various concentrations of CD25-8D8 for up to 9 days, and [3H]thymidine uptake was measured. Whereas the proliferative response of human lymphocytes to PPD was suppressed by high concentrations of CD25-8D8, subinhibitory amounts of CD25-8D8 enhanced lymphocyte proliferation by 3.5-fold (range 2.2-6.2-fold) on the second day after maximal [3H]thymidine uptake had occurred. By itself, CD25-8D8 could not induce proliferation of washed 5-day PPD-activated lymphocytes during reculturing; instead, growth enhancement by CD25-8D8 was dependent on the presence of PPD-activated culture supernatant or moderate levels of exogenous IL-2. The enhancing effect of anti-IL-2R alpha antibody, observed in both murine and human systems, reinforces the possibility that binding of IL-2 to the IL-2R alpha chain plays a negative regulatory role in signal transduction.